Lazy Investors, Discretionary Consumption, and the Cross‐Section of Stock Returns - JAGANNATHAN, RAVI; WANG, YONG (Journal of Finance, 2007)
ABSTRACT When consumption betas of stocks are computed using year‐over‐year consumption growth based upon the fourth quarter, the consumption‐based asset pricing model (CCAPM) explains the cross‐section of stock returns as well as the Fama and French (1993) three‐factor model. The CCAPM's performance deteriorates substantially when consumption growth is measured based upon other quarters. For the CCAPM to hold at any given point in time, investors must make their consumption and investment decisions simultaneously at that point in time. We suspect that this is more likely to happen during the fourth quarter, given investors' tax year ends in December.